Efficacy and Safety of Undenatured Type II Collagen in The Treatment of Osteoarthritis of The Knee: A Randomized, Double-blind, Placebo-controlled Trial - Oentarini Tjandra; Shirly Gunawan; Johan Johan; Fia Fia Lie; Marcella Erwina Rumawas; Agus Limarta (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Available medication for pain and joint stiffness release in osteoarthritis (OA) often gives considerable side effects. Undenatured type II collagen (UC-II) has been considered as a treatment for OA for its ability to prevent the progress of articular cartilage damage. Hence, this study aimed to evaluate the efficacy and safety of UC-II in modulating knee joint function.METHODS: This was a randomized, double-blind, placebo-controlled study involving 102 OA subjects. Subjects were randomized into two groups: receiving an oral daily dose of 40 mg/day UC-II or placebo containing microcrystalline cellulose for 90 days. Efficacy was evaluated by using the Western Ontario McMaster Osteoarthritis Index (WOMAC), Lequesne’s Functional Index (LFI), and Visual Analogue Scale (VAS) score on day-1, -7, -30, -60, and -90. Safety was evaluated by assessing the adverse events (AEs) and abnormal laboratory findings.RESULTS: The WOMAC total score showed a significant difference between the UC-II group vs. the placebo group from day-7 (p<0.05) to day-90 (p<0.01). UC-II was more effective in reducing the WOMAC total scores by 81.6% compared to 19.2% in the placebo group after 90 days. The total LFI and VAS score was significantly reduced in subjects supplemented with UC-II compared to the placebo group (75.8% vs. 7.8%; 67.9% vs. 12.2%, respectively). No significant changes were observed in vital signs and clinical laboratory tests compared to the placebo. The UC-II had a good safety profile with no serious adverse events among participants.CONCLUSION: UC-II significantly improved the knee pain, stiffness, and functional mobility of OA patients and was well-tolerated.KEYWORDS: osteoarthritis, undenatured type II collagen, WOMAC, VAS, LFI